Analisis Pemahaman Konsep Matematis Peserta Didik Kelas X Fase E dalam Menyelesaikan Soal Cerita Materi Eksponen dan Logaritma - Rahmadani, Chelsy; Khairi, Annisa Ummul; Rahmawati, Annisa; Nasution, Minora Longgom (Polinomial : Jurnal Pendidikan Matematika, 2025)
Mathematical conceptual understanding is essential for students, as it facilitates their ability to progress to more complex material. The aim of this study is to describe the mathematical conceptual understanding of tenth-grade high school students on the topic of exponents and logarithms. This research employs a qualitative descriptive approach using purposive sampling, involving 136 students at SMAN 7 Padang. The research instruments include an essay test on mathematical conceptual understanding consisting of 8 questions, each representing an indicator of conceptual understanding three of which are word problems as well as documentation. The results show that based on each category of mathematical conceptual understanding, the high category has a percentage of 20.59%, the medium category 62.5%, and the low category 16.91%. It can be concluded that the mathematical conceptual understanding of tenth-grade students at SMAN 7 Padang falls within the medium category.